Philosophical Thought Of Islamic Education (Challenges and Opportunities) "Essentialism And Reconstructionism - Husin, Malik; M, Amril; Dewi , Eva (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study aims to analyze the philosophical thought of Islamic education from the perspectives of essentialism and reconstructionism as an effort to address the challenges of modern education. This research employs a qualitative method with a library research approach, where the subjects are the concepts of essentialism and reconstructionism, and the object is their implementation in Islamic education. Data were collected through literature review from books, journals, and relevant scientific sources, then analyzed descriptively using content analysis techniques. The results show that essentialism in Islamic education emphasizes strengthening core values such as morality and spirituality to shape individuals with strong religious awareness, yet it faces challenges in integrating classical values with the rapid development of science and global culture. Meanwhile, reconstructionism focuses on renewing the understanding and application of Islamic values to make them more contextual and relevant amid complex social changes. The combination of both approaches creates an Islamic education paradigm that is not only strong in religious doctrine but also adaptive in responding to the demands of the times and encourages positive contributions to global society